IDENTIFIKASI RESOURCES CONSTRAINT PADA KINERJA PELAYANAN DENGAN PENDEKATAN THEORY OF CONSTRAINT DI INSTALASI RAWAT INAP RSU HAJI SURABAYA - Vida Indira Puspita; Setya Haksama (Universitas Airlangga, 2019)
The trend of Gross Death Rate (GDR) Surabaya Hajj Hospital had tended to increase from 2012 to 2015.However, it eventually decreased in 2016. This research aims to analyze the constraints in the service performance at the inpatient unit of Surabaya Hajj Hospital. The researchutilizedthe theory of constraint to minimize the constraints and to prevent the trend of increased GDR over the years. The research employed observational descriptive and cross-sectional design. The primary data were directly collected from the nurses as respondents through questionnaires. The results of the research indicated that the resource constraints were the workload, lack of facilities, lack of medical and non-medical equipment, and lack of nurse workforce. In conclusion, with all the foregoing constraints, such as the workload, lack of facilities, medical, and non-medical equipment, and lack of nurse's workforce, do not directly affect the service performance of the nurses.Accordingly, improvement efforts are recommended for the existing obstacles.